Alimentação pré-alojamento para pintos de corte descendentes de matrizes novas e velhas - Paula Costa Cardeal (2018)
It was conducted an experiment aimed to evaluated the effects of post-hatch fasting and the efficient of a pre-placement diet on broiler chickens performance, on development of gastrointestinal tract and on transfer of passive immunity for chicks from young and old broiler breeders. The experimental design a was completely randomized design in a factorial design 2X2X2, with two ages of broiler breeders (29 and 55 weeks), two placement times (24 and 48 hours) and the use or not of a pre-placement diet inside transportation boxes. Early feed stimulated the use of residual yolk sac and the initial development of gastrointestinal tract, however after placement occurred compensatory growth of these organs. The placement of chicks 48 hour after hatch had negative effects on development of duodenum mucosa, but the use of the pre-placement diet was efficient in reduced these effects. Placed chicks 48 hours after hatch enhanced broiler performance until slaughter age. The pre-placement diet enhanced broiler performance of chicks from 29 weeks old broiler breeders, besides that it reduced mortality in first week of age when chicks were placed 48 hours after hatch. Posthatch fasting did not have any effect on IgY concentration on chicks’ serum at the age of 48 hours. It was concluded that it is possible to place chicks until 48 hours after hatch, and the placement 48 hour after hatch increased body weight at the age of 37 days. Besides that, the use of pre-placement diet is indicated for broiler chicks from young broiler breeders in order to enhance broiler performance and to reduce initial mortality due to long periods of transportation.